Formulation And Antibacterial Effectiveness Test Of Ethyl Acetate And Methanol Extract Gel From Patchouli Leaf (Pogostemon Cablin Benth) Against Acne-Causing Bacteria - Muhammad Taufiq Duppa; Anshari Masri; Syafruddin; Ermawati (Afiyatun Journal of Health Sciences, 2026)
Background: Acne is an infection characterized by inflammation of the polysebocyte layer caused by microorganisms such as Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes. Antibiotic use can lead to drug resistance, making natural ingredients a viable alternative. Patchouli leaves (Pogostemon cablin Benth) contain flavonoids, saponins, and tannins with antibacterial properties. Methods: This was a laboratory experimental study involving maceration extraction of patchouli leaf using ethyl acetate and methanol solvents, followed by gel formulation and antibacterial effectiveness testing (well diffusion method) against S. aureus, S. epidermidis, and P. acnes at 3%, 5%, and 7% extract concentrations. Results: Physical stability evaluation showed all gel preparations met semisolid criteria (organoleptic, homogeneity, pH 4.5–8.0, adhesiveness >1 s, spreadability 5–7 cm, viscosity 3000–50000 cPs, thixotropic flow). At 7% concentration, ethyl acetate and methanol extracts showed the greatest inhibitory zones against all tested bacteria. Conclusion: Gel preparations of ethyl acetate and methanol extracts of patchouli leaf (Pogostemon cablin Benth) showed good physical stability and effective antibacterial activity at all concentrations, with 7% showing the highest inhibitory effect.